New methods for rendering of anaglyph stereoscopic images on CRT displays and photo-quality ink-jet printers - Tran, Vu M (University of Ottawa (Canada), 2006)
Anaglyph is considered as an inexpensive approach to display to the observer a true 3D view of a real world scene. Moreover, it is the only way of providing a 3D stereoscopic effect on ordinary paper. There are not many techniques used to render anaglyph images, and most of them are very empirical and are used exclusively for additive display devices. The mathematical Linear Projection method was proved to be the best existing method for rendering anaglyph images with high color stability and color fidelity. However, its limitation is that it can exhibit strong ghosting in the rendered anaglyph images. This study describes two separate anaglyph algorithms; one is targeted for CRT additive display devices and the other one is aimed for printer subtractive display devices. Both of these two algorithms are based on the Linear Projection method, in which they attempt to reduce the ghosting effect introduced by the Linear Projection method while maintaining the strength of the Linear Projection method. The study also characterizes the spectral forward characterization functions of a CRT monitor and a printer which are used to test the algorithms developed. The study first mathematically formulates the anaglyph phenomenon. Next, it gives a new ghosting definition which is used to derive objective functions that are used in the proposed algorithms. Besides those two algorithms, the study also introduces a test that checks the compatibility between a colored-filter glass pair and a color display device in term of the ghosting effect. The resulting rendered anaglyph images show that the ghosting effect is significantly reduced.
Keywords: Engineering, Electronics and Electrical.